2016
DOI: 10.1096/fj.201600669r
|View full text |Cite
|
Sign up to set email alerts
|

Selective p38α MAP kinase/MAPK14 inhibition in enzymatically modified LDL‐stimulated human monocytes: implications for atherosclerosis

Abstract: The first ATP-competitive p38α MAPK/MAPK14 inhibitor with excellent in vivo efficacy and selectivity, skepinone-L, is now available. We investigated the impact of selective p38α MAPK/MAPK14 inhibition on enzymatically modified LDL (eLDL) stimulated human monocytes with its implications for atherosclerosis. Among the different p38 MAPK isoforms, p38α/MAPK14 was the predominantly expressed and activated isoform in isolated human peripheral blood monocytes. Moreover, eLDL colocalized with macrophages positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…We showed that MAPKp38, ERK and NFkB activation were the top three canonical pathways in an unbiased Ingenuity pathway enriched network analysis of ELDL-treated HCASMC, and these findings were confirmed by ELISA. This is in agreement with a recent study demonstrating co-localization of immunohistochemical staining for ELDL and p38MAK/MAPK14 in human carotid endarterectomy tissue from atherosclerosis with high grade stenosis 44 . Among the wide-ranging downstream activities of phosphorylated p38MAPK, cytokine production is a component related to atherosclerosis and osteoblast differentiation 45 .…”
Section: Discussionsupporting
confidence: 93%
“…We showed that MAPKp38, ERK and NFkB activation were the top three canonical pathways in an unbiased Ingenuity pathway enriched network analysis of ELDL-treated HCASMC, and these findings were confirmed by ELISA. This is in agreement with a recent study demonstrating co-localization of immunohistochemical staining for ELDL and p38MAK/MAPK14 in human carotid endarterectomy tissue from atherosclerosis with high grade stenosis 44 . Among the wide-ranging downstream activities of phosphorylated p38MAPK, cytokine production is a component related to atherosclerosis and osteoblast differentiation 45 .…”
Section: Discussionsupporting
confidence: 93%
“…For example, MAPK 14 in module 3 was found to participate in multiple cellular processes including cell proliferation, differentiation, transcriptional regulation and development ( Young, 2013 ). Also, it can be noted that MAPK 14 may related with atherosclerosis ( Cheng et al, 2017 ). Further, BCL2 in module 2 was a therapeutic target for chronic lymphocytic leukemia since it can regulate lymphocyte in blood by hindering cell apoptosis ( Ruefli-Brasse and Reed, 2017 ; Tahir et al, 2017 ) and PGD in module 5 was related with human cervical carcinoma ( Lee et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages express various PS-specific scavenger receptors, such as Tyro3, Axl, and Mertk (collectively referred to as TAM receptors), TIM-3 and SCARF-1 that trigger the phagocytosis of dying cells and promote induction of a tolerogenic phenotype, such as the increase in IL-10 and TGFβ secretion, and a decrease in NF-κB signaling and TNFα, IL-1β, and IL-12 secretion ( 97 ). Encapsulating coagulation FVIII in PS-bearing liposomes was effective to prevent the formation of inhibitory anti-FVIII antibodies in hemophilia A animals even when animals were challenged with FVIII alone ( 53 , 57 , 98 , 99 ). A similar approach was demonstrated with alpha-glucosidase (GAA) in a mouse model of Pompe disease.…”
Section: Tolerogenic Nps That Provide Antigen Alone To Harness Naturamentioning
confidence: 99%